The Prevalence of Pornography Addiction, Self-Control, and Its Relationship with Dating Behaviour in Adolescents: A Cross-Sectional Study - Simak, Valen Fridolin; Kristamuliana; Meo, Maria Lupita Nena (Caring: Indonesian Journal of Nursing Science, 2023)
The health of adolescents is intricately linked to their adaptation process during the period of growth and development. When adolescents lack sufficient coping skills or are bewildered by these changes, it can have detrimental effects on their health. One of the main issues impacting adolescent health is pornography and sexual activities, including kissing, masturbation, and sexual intercourse. The objective of this study is to describe pornography addiction, self-control, and their relationship with adolescent dating behaviour in the city of Manado, Indonesia. The research targets adolescents in the Manado region, based on inclusion criteria that include those aged 10-19 years who are unmarried, with a sample size of 230 respondents clustered by region. The method used in this research is a cross-sectional design, involving the direct distribution of questionnaires to prospective respondents. The questionnaires consist of the Pornography Addiction Screening Tool, Brief Self-Control, and Dating Behaviour. Data were analyzed using univariate and bivariate analysis, using the chi-square test. The results of this study showed that the level of normal pornography addiction 96.5%, risk of addiction 2.6%, vulnerable to addiction 0.9%, and addiction 0%. Bivariate analysis demonstrated a significant relationship between pornography addiction, self-control, and dating behaviour with a p-value of <0.05. The contribution of the results of this research to the field of community health, can serve as foundational data to support ongoing health promotion efforts. This includes the development of technology, as well as the strengthening of policies and adolescent health programs in schools and community health centres.